Blink reflex changes and sensory perception in infraorbital nerve-innervated areas following zygomaticomaxillary complex fractures - Young Sook Park; Jaehoon Choi; Sang Woo Park (Archives of Plastic Surgery, 2020)
Background Infraorbital nerve dysfunction is commonly reported after zygomaticomaxillary complex fractures. We evaluated sensory changes in four designated areas (eyelid, nose, zygoma, and lip) innervated by the infraorbital nerve. This evaluation was conducted using the static two-point discrimination test and the vibration threshold test. We assessed the diagnostic significance of the blink reflex in patients with infraorbital nerve dysfunction. Methods This study included 18 patients, all of whom complained of some degree of infraorbital nerve dysfunction preoperatively. A visual analog scale, the infraorbital blink reflex, static two-point discrimination, and the vibration threshold were assessed preoperatively, at 1 month postoperatively (T1), and at a final follow-up that took place at least 4 months postoperatively (T4). The results were analyzed using a multilevel generalized linear mixed model. Results Scores on the visual analog scale significantly improved at T1 and T4. The infraorbital blink reflex significantly improved at T4. Visual analog scale scores improved more rapidly than the infraorbital blink reflex. Two-point discrimination significantly improved in all areas at T4, and the vibration perception threshold significantly improved in the eyelid at T4. Conclusions Recovery of the infraorbital blink reflex reflected the recovery of infraorbital nerve dysfunction. We also determined that the lip tended to recover later than the other areas innervated by the infraorbital nerve.